Clinical Guidelines 2.0: Translation of Tables 2 and 3 and Apendix 1 of Schünemann HJ et al. CMAJ. 2014; 186:E123-42. - Santos, Guilherme Ferreira dos (2015)
Clinical Practice Guidelines are instruments to support decision to improve the quality of clinical care. An expert group from McMaster University (Canada) has developed - from high-quality literature sources – a guidance on the practical steps for their development, dissemination, implementation and evaluation. This is the 1st time anyone seeks to bring together in one document all information regarding the Clinical Practice Guidelines. Due to the interest of this paper, the Centre for Evidence Based Medicine at the University of Lisbon School of Medicine contacted the authors of the article and the journal where it was published (the Canadian Medical Association Journal) in order to translate the most relevant parts of the article (including the practice tables), which was agreed. This guide should be useful to those who, being interested in the development, dissemination and implementation of Clinical Practice Guidelines, want to ensure their intrinsic quality based on relevant and updated evidence.